2014
DOI: 10.1021/ja506688m
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Condensation Network of Organosiloxanes on Nanoparticles using 2D 29Si–29Si Solid-State NMR Enhanced by Dynamic Nuclear Polarization

Abstract: Silica (SiO2) nanoparticles (NPs) were functionalized by silanization to produce a surface covered with organosiloxanes. Information about the surface coverage and the nature, if any, of organosiloxane polymerization, whether parallel or perpendicular to the surface, is highly desired. To this extent, two-dimensional homonuclear (29)Si solid-state NMR could be employed. However, owing to the sensitivity limitations associated with the low natural abundance (4.7%) of (29)Si and the difficulty and expense of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(132 citation statements)
references
References 48 publications
5
127
0
Order By: Relevance
“…Amorphous materials such as silicas (SiO 2 ) can exhibit inhomogeneous broadening at RT to such an extent that the DNP conditions make little difference, and have thus already been extensively studied with this technique [29,46,[59][60][61][62]. Furthermore, extremely rigid systems [44] and systems with nuclei of interest with a relatively large quadrupolar coupling, such as 27 Al [36][37][38] and 17 O [6], will also experience little change in resolution upon addition of DNP matrices and polarizing agents and are therefore also highly pertinent for MAS-DNP studies.…”
Section: Resolutionmentioning
confidence: 99%
“…Amorphous materials such as silicas (SiO 2 ) can exhibit inhomogeneous broadening at RT to such an extent that the DNP conditions make little difference, and have thus already been extensively studied with this technique [29,46,[59][60][61][62]. Furthermore, extremely rigid systems [44] and systems with nuclei of interest with a relatively large quadrupolar coupling, such as 27 Al [36][37][38] and 17 O [6], will also experience little change in resolution upon addition of DNP matrices and polarizing agents and are therefore also highly pertinent for MAS-DNP studies.…”
Section: Resolutionmentioning
confidence: 99%
“…The advent of Dynamic Nuclear Polarization (DNP), using gyrotron microwave (MW) sources, combined with MAS has opened the door to many advanced studies of solids at high magnetic fields [1]. The development and implementation of high field gyrotrons up to the Terahertz range has enabled the construction of high field MAS-DNP instruments, and led to the commercialization of MAS-DNP spectrometers by Bruker Inc. [2] operating up to 18 T. Theses high field DNP instrument developments have triggered a vast interest of the solid-state NMR community in MAS-DNP experiments, both for biological [3][4][5][6][7][8][9][10][11] and material science [12][13][14][15][16][17][18][19][20][21][22] applications. Most of these experiments performed today are using nitroxide based bi-radicals such as TOTAPOL [23,24,2,8,25,26,9], and recently new nitroxide based biradicals have been introduced with varying longitudinal relaxation times, phase memory times (or transverse relaxation time), electron-electron dipolar couplings, and relative gÀtensor orientations such as AMUPOL, bCTbK, or TEKPOL [27,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Notably, Emsley and co-workers recently showed that by combining DNP-enhanced 2D HETCOR experiments and REDOR-based dipolar coupling measurements it was possible to determine the three-dimensional structure of molecules grafted onto silica surfaces ( Figure 3A). 27 DNP-enhanced 2D 29 Si- 29 Si correlation experiments were used to observe the bonding/connectivity of silicon atoms at the silica surface ( Figure 3B) 28 and probe the spatial distribution of organic fragments on functionalized silica surfaces. Grey and co-workers showed that for direct 17 O NMR experiments on 17 O-labelled CeO 2 the surface layers showed faster polarization build-up and higher signal enhancement.…”
mentioning
confidence: 99%